Use of urinary NGAL in steroid-resistant vs. steroid-sensitive nephrotic syndrome: a systematic review and meta-analysis - Aymen Abdalla; Abdelrahman Ali; I. O. Abufatima; Saeed Majzoub; Tasneem A. E. Elbasheer; Sara M. A. O. Ahmed; Seima Osman; Yousra K. K. Khalid; Ahmed Elamir; Hiba K. K. Khalid; Nihal M. A. Abdelmutalib; Sagad O. O. Mohamed (BMC Nephrology)
Abstract Background Nephrotic syndrome is a common glomerular disorder. Treatment typically begins with corticosteroids, but patient response varies. Differentiating between steroid-sensitive nephrotic syndrome (SSNS) and steroid-resistant nephrotic syndrome (SRNS) early in the disease course is important, as SRNS is associated with a higher risk of poor long-term outcomes. Neutrophil gelatinase-associated lipocalin (NGAL), a biomarker released in response to tubular injury, has emerged as a potential non-invasive marker for renal damage. Methods We conducted a systematic review and meta-analysis of studies reporting NGAL levels in SSNS and SRNS, based on the PRISMA guidelines. A comprehensive literature search was conducted using PubMed, Scopus, Web of Science, ScienceDirect, and the WHO Virtual Health Library Regional. The statistical analysis was performed using a random-effects model to estimate the standardized mean difference (SMD) with a 95% confidence interval. Results A total of 16 studies were included. Meta-analyses revealed significantly higher urinary NGAL levels in both SSNS and SRNS patients compared to healthy controls. Urinary NGAL levels were significantly higher in SSNS and SRNS patients compared to healthy controls, with SMD = 0.78 (95% CI: 0.434–1.128, P < .001) and SMD = 2.56 (95% CI: 1.152–3.971, P < .001), respectively. Patients with SRNS had markedly higher urinary NGAL levels than those with SSNS (SMD = 1.889, 95% CI: 0.819–2.959, P < .001). ROC analyses across several studies demonstrated moderate to strong discriminative ability of urinary NGAL in distinguishing between SRNS and SSNS. Conclusion Urinary NGAL demonstrated strong potential as a non-invasive biomarker for distinguishing between SRNS and SSNS, supporting its clinical utility in early diagnosis, risk stratification, and management.